PELAKSANAAN PASRAMAN KILAT SEBAGAI PENDIDIKAN AGAMA BERBASIS MASYARAKAT DI PURA GIRI NATA KABUPATEN KEDIRI - Made Dwianan Mustawan (Lembaga Penerbit Sekolah Tinggi Hindu Dharma Klaten, 2019)
Developing the lightning era as an effort to fill the lack of religious education in the family and school environment to avoid the moral and spiritual deterioration of the younger generation. Lightning Pasraman or religious guidance activities for Hindus during school holidays to increase faith and devotion to God Almighty and mental spiritual formation for students and Hindu teenagers (Hindu young generation). Based on this there are three problems that can be proposed in this study, namely; 1) What is the perception of the community with the existence of lightning security in Giri Nata Temple, 2) What is the contribution felt by the community after the Hindu religious education in the lightning days in Giri Nata Temple, 3) What are the obstacles and support in learning Hinduism in the lightning era in Giri Nata Temple. Methodologically this research uses qualitative and interpretive descriptive techniques. The theory used in assessing the problems in this research is structural theory of functionalism, constructivist theory, and behavioristic theory. The results of this study indicate that (1) the public's perception of the lightning era, where the lightning market is a place for Hindus to increase Hindu religious knowledge so that it can be applied in the life of society and state. (2) Contribution felt by the community towards religious learning in the lightning era, where religious learning aims to increase knowledge quickly in order to increase faith, understanding, appreciation of students about Hinduism, and (3) Obstacles and support in the management process in the lightning season internally due to the weakness of the pasraman management in planning programs to meet the needs, the last obstacle is the low awareness of students to participate in activities in the lightning era.